A teacher for all generations essays in honor of James C. Vanderkam - Mason, Eric Farrel 1969-; VanderKam, James C. 1946- (Leiden Boston Brill, 2012)
Pt. 1. The Hebrew Bible and the ancient Near East -- pt. 2. Qumran and the Dead Sea scrolls -- pt. 3. Early Judaism -- pt. 4. Studies on Enoch and Jubilees -- pt. 5. The New Testament and early Christianity
"This collection of essays honors James C. VanderKam on the occasion of his sixty-fifth birthday and twentieth year on the faculty of the University of Notre Dame"--ECIP data view. - Includes bibliographical references and indexes
Keywords: Ethiopic book of Enoch -- Criticism, interpretation, etc; Book of Jubilees -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Dead Sea Scrolls; Ethiopic book of Enoch -- Criticism, interpretation, etc; Book of Jubilees -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Qumran community; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Festschrift; Konferenzschrift